2021
DOI: 10.1101/2021.06.16.448511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of dietary exposure to pesticides on faecal microbiome metabolism in adult twins

Abstract: Concerns have been raised as to whether the consumption of foodstuffs contaminated with pesticides can contribute to the development of chronic human diseases by affecting microbial community function in the gut. We provide the first associations between urinary pesticide excretion and the composition and function of the faecal microbiome in 65 twin pairs in the UK. Biomonitoring of exposure to 186 common insecticide, herbicide, or fungicide residues showed the presence of pyrethroid and/or organophosphorus in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 103 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…For example, it posed serious health risks to humans, damaged biodiversity and the environment, increased bioaccumulation of pesticide residues in the food chain, killed pollinators, polluted water and air, influenced changes in the microbiome to reduce mammalian resistance to pathogens, and the emergence of resistant insect (Mahmood et al 2016;Tarar 2019;Syromyatnikov et al 2020;Kalyabina et al 2021;Riyaz et al 2022). Mesnage et al (2021) found 186 pesticide residues from the pyrethroid and organophosphate groups in human urine samples. According to World Health Organization (WHO), every year, there are three million cases of poisoning by synthetic pesticides, which cause the death of about 220,000 people (Mughal 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it posed serious health risks to humans, damaged biodiversity and the environment, increased bioaccumulation of pesticide residues in the food chain, killed pollinators, polluted water and air, influenced changes in the microbiome to reduce mammalian resistance to pathogens, and the emergence of resistant insect (Mahmood et al 2016;Tarar 2019;Syromyatnikov et al 2020;Kalyabina et al 2021;Riyaz et al 2022). Mesnage et al (2021) found 186 pesticide residues from the pyrethroid and organophosphate groups in human urine samples. According to World Health Organization (WHO), every year, there are three million cases of poisoning by synthetic pesticides, which cause the death of about 220,000 people (Mughal 2018).…”
Section: Introductionmentioning
confidence: 99%